Contextual-based Digital Comic with Mathematics Content of Angle Measurement Material for Grade V Elementary School Students - Putu Alvina Damayanthi; Gusti Ngurah Sastra Agustika; I Nyoman Laba Jayanta (International Journal of Elementary Education, 2025)
This research departs from the fact that the lack of use of digital media in the learning process. Research with this development model aims to provide alternative learning media in the form of contextual-based digital comics on grade V angle measurement material to improve student learning outcomes. This research was conducted using the ADDIE model which consists of the stages of analysis, planning, development, implementation, and evaluation. The subjects selected in this study consisted of one content expert, design expert, media expert, fifth grade teacher, three individual test students, and nine students for the small group test. The data in this study were collected through interviews, questionnaires, and tests. The instruments used in this study were questionnaires and multiple choices tests. The data that has been collected is then analysed using analysis techniques with quantitative descriptive approaches, qualitative descriptive, inferential statistical analysis. The findings in this digital comic product development research are as follows: (a) The results of product validity test through experts show that digital comic media have very valid qualifications; (b) the results of practicality test through teacher responses, individual tests, and small group tests obtained very practical qualifications; (c) the results of media effectiveness test through pre-test and post-test obtained effective qualifications. It can be concluded that the contextual-based digital comic media for mathematics content on angle measurement material is effective in improving learning outcomes, especially for grade V students.